Design and manufacture the gearing and burning system for the diesel furnace - Amirulhamzah, Zainuddin (2008)
This thesis regards on designing and manufacturing the gearing and burning system of the diesel furnace which include several specifications. The gearing and burning system of a diesel furnace can be various from type of furnace to the scale of the furnace itself. The furnace body or methods of transfer are which affects most on this project. It is by tilting the furnace body to pour the molten metal into a transferring cup which made existed such a system. To hold the furnace body into a pouring position, a gearing system must be made to tilt or move the furnace body. It is also crucial to hold it within its pouring position which enquires a locking mechanism. In this type of furnace application, the burner plays it part as a blower which transfers heat into the furnace body. This burner is attached to fuel pipeline from a source. Regarding this project, the matter is designing the frame to hold the entire components. The frame has been design so that it can withstand weight even pressure and also able to function properly when in use. The frame also consists of resistance materials which can overcome heat during its period of heating. From many analysis and references on frame design has result in a stable and durable frame to hold the entire components and able to function properly as a platform.